Whole body MRI, including diffusion-weighted imaging in follow-up of patients with testicular cancer. (26th November 2015) - Mosavi, Firas; Laurell, Anna; Ahlström, Håkan
Abstract : Background. Whole body (WB) magnetic resonance imaging (MRI), including diffusion-weighted imaging (DWI) has become increasingly utilized in cancer imaging, yet the clinical utility of these techniques in follow-up of testicular cancer patients has not been evaluated. The purpose of this study was to evaluate the feasibility of WB MRI with continuous table movement (CTM) technique, including multistep DWI in follow-up of patients with testicular cancer. Patients and methods. WB MRI including DWI was performed in follow-up of 71 consecutive patients (median age, 37 years; range 19–84) with histologically confirmed testicular cancer. WB MRI protocol included axial T1-Dixon and T2-BLADE sequences using CTM technique. Furthermore, multi-step DWI was performed using b-value 50 and 1000 s/mm 2 . One criterion for feasibility was patient tolerance and satisfactory image quality. Another criterion was the accuracy in detection of any pathological mass, compared to standard of reference. Signal intensity in DWI was used for evaluation of residual mass activity. Clinical, laboratory and imaging follow-up were applied as standard of reference for the evaluation of WB MRI. Results. WB MRI was tolerated in nearly all patients (69/71 patients, 97%) and the image quality was satisfactory. Metal artifacts deteriorated the image quality in six patients, but it did not influence the overall results. No case of clinical relapse was observed during the follow-up time. There was a good agreement between conventional WB MRI and standard of reference in all patients. Three patients showed residual masses and DWI signal was not restricted in these patients. Furthermore, DWI showed abnormally high signal intensity in a normal-sized retroperitoneal lymph node indicating metastasis. The subsequent 18 F-FDG PET/CT could verify the finding. Conclusion. WB MRI with CTM technique including multi-step DWI is feasible in follow-up of patients with testicular cancer. DWI may contribute to important added-value data to conventional MRI sequences regarding the activity of residual masses.